2011
DOI: 10.1021/nl2021653
|View full text |Cite
|
Sign up to set email alerts
|

A New Route toward Semiconductor Nanospintronics: Highly Mn-Doped GaAs Nanowires Realized by Ion-Implantation under Dynamic Annealing Conditions

Abstract: We report on highly Mn-doped GaAs nanowires (NWs) of high crystalline quality fabricated by ion beam implantation, a technique that allows doping concentrations beyond the equilibrium solubility limit. We studied two approaches for the preparation of Mn-doped GaAs NWs: First, ion implantation at room temperature with subsequent annealing resulted in polycrystalline NWs and phase segregation of MnAs and GaAs. The second approach was ion implantation at elevated temperatures. In this case, the single-crystallini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…In this work, we concentrate on the higher doped wires. The NW growth and implantation techniques were discussed in detail previously [13].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we concentrate on the higher doped wires. The NW growth and implantation techniques were discussed in detail previously [13].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…An exciting new direction, which has recently been shown to be possible due to successful incorporation of magnetic Mn dopants into epitaxially grown GaAs nanowires (NWs) [4][5][6][7][8][9][10][11], is their use for proofof-concept spintronics devices [12]. The doping techniques are advancing rapidly, and it has recently been shown that ion beam implantation can produce single crystalline, homogeneously doped GaMnAs NWs [13]. Furthermore, a recent study found that the Curie temperature of GaMnAs nanostrips could be enhanced to 200 K with nanostructure engineering [14], suggesting the possibility for nanowirebased devices to operate at higher temperatures compared to thin films or bulk.…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions lighter (Ga,Al)As appear darker. STEM images taken along the [11][12][13][14][15][16][17][18][19][20] zone axis permit to determine clearly the interfaces between different shells along the NW length. The tomography was performed with the following parameters: electron probe size 0. paramagnetic test sample) are achieved by degaussing the magnetometer with an oscillating magnetic field of decreasing amplitude.…”
Section: Tem Imaging and Elemental Mappingmentioning
confidence: 99%
“…7 These options are all well encompassed within a bottom-up approach: a controlled growth of ferromagnetic nanowires of (preferably) semiconductor origin, may serve as an ideal route to provide the necessary architecture and resulting functionalities. This is predominantly the reason of the strong ongoing interest in the elaboration of nonequilibrium growth of (Ga,Mn)As dilute ferromagnetic semiconductor (DFS) nanowires (NWs) [8][9][10][11][12][13][14][15][16][17][18][19][20][21] which would exhibit or even surpass the excellent micromagnetic properties of the prototype, epitaxial (Ga,Mn)As layers. 22 This challenge has proven to be a formidable one.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the annealing temperature ordinarily keeps at two thirds of the melting point of the implanted materials [18]. Lately, Borschel et al [19] reported that GaAs nanowires implanted by Mn + at 250°C remained as single crystalline. However, polycrystalline nanowires were acquired after implantation at room temperature with subsequent annealing.…”
Section: Reviewmentioning
confidence: 99%